Surgically induced astigmatism following manual small incision cataract surgery versus phacoemulsification in age-related cataract: a comparative analysis - Oyekunle, Idris; Okonkwo, Ogugua; Ogbonnaya, Chimdia; Onwuegbuna, Arinze; Akinye, Ayodele; Abdu, Lawan; Ogundipe, Bade; Oshunkoya, Lateefat; Hassan, Kunle (Transactions of the Ophthalmological Society of Nigeria, 2025)
BACKGROUND Cataract surgery is among the most common and successful procedures globally.1,2 While phacoemulsification is the more advanced method, manual small incision cataract surgery (MSICS) remains prevalent in developing countries due to its affordability, shorter duration, and comparable visual outcomes.3-5 There is limited comparative data from Nigeria on corneal astigmatism and refractive stability between MSICS and phacoemulsification. This study aims to compare these outcomes between the two techniques. MATERIALS AND METHODS The study was a prospective hospital-based, comparative study of consecutive patients with age-related cataracts, randomized into 2 groups by randomly assigning letters A and B in a ratio of 1:1 to undergo MSICS (group A) or phacoemulsification (group B) using the superior approach, comparing the surgically induced corneal astigmatism (SIA) between the two techniques. SIA was calculated through vector analysis using the Warren Hill SIA calculator and the Holladay SIA method while stable corneal astigmatism was defined as average keratometry readings (average K in dioptres) within ± 0.50D6 and axis within 30 degrees of the last follow-up.7 The results were compared between the two groups, with a p-value of less than 0.05 indicating statistical significance. Ethical approval was obtained from the Lagos State University Teaching Hospital Health Research Ethical Committee (HREC) and written informed consent was obtained from the patients. RESULTS A total of 214 eyes were studied, with 107 in each surgical group. Age and gender distribution were similar (p=0.153 and 0.218) as seen in Table 1. Preoperative against-the-rule (ATR) astigmatism was more common in the phacoemulsification group (66.4%) than in the MSICS group (47.7%). By month 3, ATR astigmatism increased to 76.6% in the MSICS group compared to 49.5% in the phacoemulsification group. As shown in Table 2, the mean SIA in the MSICS group at months 1, 2 and 3 was 1.94D x 19.3o, 1.83D x 18.2o and 1.72D x 20.2o, respectively, while in the phacoemulsification group, the mean SIA was 0.92D x 17.7o, 1.01D x 16.4o and 1.00D x 15.8o at months 1, 2 and 3, respectively. SIA differed significantly between the two groups at all postoperative time points (p<0.001). Final best corrected visual acuity was similar at month 3, with 95.3% of MSICS and 98.1% of phacoemulsification patients achieving 6/12 or better (p=0.324). By the first postoperative month, 96 eyes (89.7%) in the MSICS group and 89 eyes (83.2%) in the phacoemulsification group had achieved stable corneal astigmatism. By the second month, stability was observed in 95 eyes (88.8%) of the MSICS group and 106 eyes (99.1%) of the phacoemulsification group (Figure 1). DISCUSSION This study found that postoperative ATR increased significantly among MSICS patients compared to phacoemulsification, a finding in line with earlier studies8,9 and likely due to larger incisions, wound construction, and cauterization in MSICS. Surgically induced astigmatism (SIA) was consistently higher in MSICS at all follow-up points, in line with previous evidence by Waghmare et al9, and Nair et al.10 Although more of the MSICS eyes stabilized by 1 month compared to phacoemulsification eyes, nearly all phacoemulsification eyes stabilized by the second month. Both procedures produced excellent visual outcomes, with over 96% of MSICS and 98% of phacoemulsification patients achieving 6/12 or better by three months. Nonetheless, phacoemulsification provided slightly better unaided visual acuity, reducing the likelihood of dependence on corrective lenses. CONCLUSION Phacoemulsification resulted in lower and more stable SIA. However, both techniques provided excellent final visual outcomes. While Phacoemulsification is more desirable, MSICS is relevant in resource-limited settings.